2014
DOI: 10.1007/s11427-014-4613-6
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-induced myofibroblast-like conversion of engrafted keratinocytes

Abstract: Myofibroblasts, recognized classically by -smooth muscle actin (-SMA) expression, play a key role in the wound-healing process, promoting wound closure and matrix deposition. Although a body of evidence shows that keratinocytes explanted onto a wound bed promote closure of a skin injury, the underlying mechanisms are not well understood. The basal layer of epidermis is rich in undifferentiated keratinocytes (UKs). We showed that UKs injected into granulation tissue could switch into -SMA positive cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…Furthermore, the mesenchymal features of these cells were reduced in the P311 KO mouse burn wounds. In this study, we found that superficial second-degree thermal burn wounds in mice healed within 10 days and α-SMA + cells were not detected in the epidermis of these mice, consistent with the results of previous studies [14, 15]. However, the burn wounds obtained from patients who needed skin graft surgery healed slower than the mouse wounds, and α-SMA + cells were observed in the wounds of these patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the mesenchymal features of these cells were reduced in the P311 KO mouse burn wounds. In this study, we found that superficial second-degree thermal burn wounds in mice healed within 10 days and α-SMA + cells were not detected in the epidermis of these mice, consistent with the results of previous studies [14, 15]. However, the burn wounds obtained from patients who needed skin graft surgery healed slower than the mouse wounds, and α-SMA + cells were observed in the wounds of these patients.…”
Section: Discussionsupporting
confidence: 92%
“…In skin, epidermal cells are classically thought to perform their role in myofibroblast formation by secreting transforming growth factor beta 1 (TGFβ1), interleukin-1 (IL-1), basic fibroblast growth factor (bFGF), tumor necrosis factor alpha (TNFα), and other humoral factors that regulate the fibroblast to myofibroblast differentiation [1113]. Recently, several studies have shown that epidermal keratinocytes directly transdifferentiate into fibroblasts when exposed to TGFβ1, IL-1β, TNFα, and fetal bovine serum (FBS) [14–16]. However, the mechanisms involved in keratinocyte transdifferentiation during wound healing are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…As in previous studies, a subset of intestinal subserosal LMW‐CK (+)/vimentin (+)/SMA (+) fibroblasts was observed, potentially indicating transformation of the mesothelial cavitary lining to subserosal fibroblasts (mesothelial‐mesenchymal transition) . Interestingly, the unusual pattern of SMA positivity in the basal layer, seen in 2 skin biopsies, raises the possibility of cutaneous epithelial‐mesenchymal transition (EMT), supporting the theory that stimulated basal keratinocytes are capable of myofibroblastic differentiation . Although artefactual staining cannot be excluded, the lack of keratinocyte staining with SMA in control tissue or other skin biopsies and the membranous staining pattern characteristic of true SMA positivity does not favor this.…”
Section: Discussionsupporting
confidence: 78%
“…An efficient re-epithelialization is required for wound repair (Eckert et al, 2002). In the skin, re-epithelialization is accomplished by keratinocyte proliferation, migration, stratification, and differentiation (Laplante et al, 2001;Li et al, 2014). Among these, the proliferation and differentiation of keratinocytes enable skin stratification, thus promoting wound closure and forming a physical barrier (Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%